COVID-19 PANDEMIC AND THE REALITIES OF POVERTY IN NIGERIA: A POLITICAL ECONOMY INTERPRETATION - OYEFOLU, Samson (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The novel Coronavirus disease affects the poverty level in Nigeria. It has reduced the standard of living of the people and caused unemployment among other social-economic woes. This is against the backdrop of the country’s rating as the poverty capital of the world with an estimated 87 million people living on less than the 2 a day threshold. Thus, this article examines the COVID-19 pandemic and the realities of poverty in Nigeria within the framework of the political economy. While relying on secondary data and descriptive analysis, the paper argues that covid-19 obviously exposed the realities of poverty in Nigeria under the prevailing global health emergency. The pandemic has induced a decline in the global oil price which is the mainstay of the economy. This has had a devastating impact on an already weak and underdeveloped digital economy for the smooth running of educational curriculum, and businesses. This reality is compounded by the extant poor state of infrastructure in the public health sector, lack of national welfare programmes, an alarming rate of poverty, and unemployment. The study concludes that the precarious socio-economic realities are a function of the country’s neocolonial character of the Nigerian state. Without viable production, the country depends solely on the oil sector for rent collection while oppressing and exploiting the mass of the people. This article then recommends drastic measures to diversify the economy, revamp infrastructure in the public health sector including the pharmaceutical industry, transform the ideological character of the state, improve the digital economy, and articulate national welfare programmes.